2004
DOI: 10.2807/esm.09.12.00493-en
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis surveillance in France, 2000-2003

Abstract: This article describes syphilis trends, characteristics of patients from 2000 to 2003 in France and trends of the benzylpenicillin benzathine 2.4 million UI sales from 2001 to 2003. The ongoing surveillance system for syphilis case reporting since 2001 has been set up in volunteer settings, mostly public settings where STI treatment is offered. Clinical case reporting is complemented by sexual behavioural data based on a self-administered questionnaire. From 2000 to 2003, 1089 syphilis cases were reported in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 0 publications
2
22
0
2
Order By: Relevance
“…Also MSM with current syphilis are 3.8 times more likely to have had more than ten sex-partners in the past 12 months than MSM without current syphilis. The change in sexual behaviour with more risk-taking practices is likely to have contributed to the recent increase in STIs in Europe [9,19,20,22]. This supports the need for improved preventive work with adapted health prevention messages and education for MSM.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Also MSM with current syphilis are 3.8 times more likely to have had more than ten sex-partners in the past 12 months than MSM without current syphilis. The change in sexual behaviour with more risk-taking practices is likely to have contributed to the recent increase in STIs in Europe [9,19,20,22]. This supports the need for improved preventive work with adapted health prevention messages and education for MSM.…”
Section: Discussionmentioning
confidence: 81%
“…It can be assumed that MSM to a larger extent choose to live in big cities since they assure more anonymity and less stigmatisation for MSM. Big cities also supply a meeting ground for sexual networks that facilitate the spread of STIs, as has been reported from other European Union countries [17][18][19][20]. A study in Sweden on risk factors for syphilis among MSM showed that current syphilis patients are 7.8 times more likely to have had syphilis in the last five years than MSM without current syphilis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple complications of syphilis may appear, including gumma, neurosyphilis, and cardiovascular syphilis. There has been an increase in the frequency of early syphilis in most Western countries since 2000 (7), the affected population being characterized by a high proportion of men having sex with men (MSM) and the overrepresentation of HIV-infected patients (almost 50% in our experience) (11,12).…”
mentioning
confidence: 99%
“…An estimated 12 million new syphilis cases occur globally each year, the majority of which are in developing nations (20). In recent years, there has been a resurgence of syphilis in many developed countries, particularly among populations of men who have sex with men, with notable outbreaks spreading rapidly across North America, Europe, and Australia (1,8,11,25,44). Existing public health measures are not successfully controlling the spread of this disease, and alternative means of syphilis prevention are needed.…”
mentioning
confidence: 99%